Circadian variation and in vitro cytotoxic activity evaluation of volatile compounds from leaves of Piper regnellii (Miq) C. DC. var. regnellii (C. DC.) Yunck (Piperaceae). Issue 7 (3rd April 2018) - Anderson, Roseli R.; Girola, Natalia; Figueiredo, Carlos R.; Londero, Vinicius S.; Lago, João Henrique G.
Abstract: Aiming detection of circadian variation in the chemical composition of volatiles from Piper regnellii, the leaves were collected during four different periods (8, 12, 16 and 20 h) in the same day. After extraction by hydrodistillation and GC/MS analysis, no significant variation was observed for the main compounds: germacrene D (45.6 ± 1.5–51.4 ± 3.1%), α–chamigrene (8.9 ± 1.3–11.3 ± 2.7%) and β–caryophyllene (8.2 ± 0.9–9.5 ± 0.3%). Evaluation of in vitro cytotoxicity against several cancer and non-tumourigenic cells indicated promising activity, especially to HeLa (human cervical carcinoma) with IC50 ranging from 11 ± 3 to 17 ± 3 μg/mL. The obtained volatile oils were pooled and subjected to fractionation to afford pure β-caryophyllene, α-chamigrene and germacrene D, being this last compound the more active against HeLa cells with IC50 of 7 ± 1 μg/mL (34 ± 5 μM). Therefore, the predominance of germacrene D in all analysed oils could justify, at least in part, the activity observed for the volatile compounds from P. regnellii leaves. Abstract :